Quantum information, computation and communication - Jones, J. A. (Jonathan A.); Jaksch, Dieter (Cambridge : Cambridge University Press, 2012)
'Quantum physics allows entirely new forms of computation and cryptography, which could perform tasks currently impossible on classical devices, leading to an explosion of new algorithms, communications protocols, and suggestions for physical implementations of all these ideas. As a result, quantum information has made the transition from an exotic research topic to part of mainstream undergraduate courses in physics. Based on years of teaching experience, this textbook builds from simple fundamental concepts to cover the essentials of the field. Aimed at physics undergraduate students with a basic background in quantum mechanics, this textbook guides readers through theory and experiment, introducing all the central concepts without getting caught up in details. Worked examples and exercises make the textbook useful as a self-study text for those who want a brief introduction before starting on more advanced books. Solutions are available online at www.cambridge.org/9781107014466'--
Includes bibliographical references and index.
Keywords: Quantum computers -- Textbooks; Information theory in physics -- Textbooks